Study of IL4‐590C/T and IL6‐174G/C Gene Polymorphisms in Type 2 Diabetic Patients With Chronic Kidney Disease in North Indian Population - Neelofar, Km; Ahmad, Jamal; Ahmad, Arif; Alam, Khursheed (Journal of cellular biochemistry, 2017)
ABSTRACT To explore the associations between potential functional promoter polymorphisms in pro‐inflammatory and anti‐inflammatory (IL‐4(‐590C/T) and IL‐6(‐174G/C) cytokine genes, and kidney dysfunction in North Indian type 2 diabetic subjects with chronic kidney disease. A total of 150 subjects aged 25–75 year were included in this study. The glomerular filtration rate (GFR) and serum creatinine were estimated. PCR was performed to analyse genotype distribution in IL‐4 (‐590T/C) and IL‐6 (‐174G/C) among healthy, type 2 diabetic patients with or without CKD. The genotype distributions were determined by Hardy–Weinberg equilibrium. CKD patients showed lower GFR (59.36 ± 1.33 ml/min/1.73 m2) and higher serum creatinine (1.93 ± 0.99% mg) level in comparison to diabetic patients without CKD and healthy subjects. Genotypic distribution of the different genotypes among the study groups in IL‐4 gene was genotype CC = 30, TC = 12, and TT = 8 in CKD patients. In type 2 diabetic patients without CKD, genotype distribution was CC = 38, TC = 10, and TT = 2. In healthy subjects, distribution of genotype was CC = 35, TC = 14, and TT = 1. The distribution of different genotype among the study groups for IL‐6 gene was GG = 27, GC = 20, and CC = 3 in healthy subjects; GG = 28, GC = 19, and CC = 3 in diabetic patients without CKD and GG = 38, GC = 11, and CC = 1 in diabetic patients with CKD. There was no significant difference in the distribution of genotype frequencies between healthy subjects and diabetic patients without CKD but a significant difference was found in diabetic patients with CKD. The functional promoter polymorphisms IL4‐590C/T and IL6‐174G/C, which affect the IL‐4 and IL‐6 levels in north Indian subjects, were associated with kidney dysfunction and CKD. J. Cell. Biochem. 118: 1803–1809, 2017. © 2016 Wiley Periodicals, Inc. The associations between common potential functional promoter polymorphisms in pro‐inflammatory and anti‐inflammatory (IL‐4(‐590C/T) and IL‐6(‐174G/C) cytokine genes and kidney dysfunction in north Indian type 2 diabetic patients with chronic kidney disease.